Trinity Church under construction, Boylston Street,1874 - Unknown (Tufts Archival Research Center, 2005)
Elevated view looking southwest of the construction area of Trinity Church. The street running diagonally behind the construction is Huntington Avenue. The light colored buildings in the center of the image are on the corner of Huntington Avenue and Dartmouth Street. On the far left in this image is a partial view of the Museum of Fine Arts under constuction. 5 1/2 x 8 1/8 Photographs